Desenvolvimento de um conector de cisalhamento em chapa dentada para estruturas mistas de aço e concreto e estudo do seu comportamento - Gustavo de Souza Verissimo (2007)
This work presents the design of a shear connector for steel and concrete composite structures and an investigation of its structural behavior based on push-out test results. This shear connector consists on a steel rib with indentation that provides resistance to longitudinal shear and prevents transversal separation between the concrete slab and the steel profile (uplift). The present study comprised a large investigation to define the new connector geometry, an experimental program, the derivation of an expression for predicting the connector capacity, as well as the training of artificial neural networks toforecast the connector response under diverse conditions. The experimental program, with 41 push-out tests according to EN 1994-1-1:2004, was divided into three phases to investigate the connection behaviour. The connection capacity and ductility, as well asthe failure mechanisms observed were evaluated, regarding the influence of several parameters. The results showed that the proposed connector presents an adequate structural performance, with high stiffness for service loads and good ductility in ultimate limit state, constituting an alternative to existing shear connectors like the stud bolts and the Perfobond.